Allyship as action : 7 ways to advocate for others - Boteju, Tanya (Orca take action!, 2025)
"Part of the nonfiction Orca Take Action series for middle-grade readers, this illustrated book introduces young readers to what it means to be an ally and realistic actions they can take to practice allyship in their own lives."--